Synthesis and Anti-mycobacterium Study on Halo-substituted 2-aryl oxyacetohydrazones - Desale, Vijay J.; Mali, Suraj N.; Chaudhari, Hemchandra K.; Mali, Maya C.; Thorat, Bapu R.; Yamgar, Ramesh S. (Current Computer - Aided Drug Design, 2020)
Background: The treatment of multiple-drug-resistant tuberculosis (MDR-TB) with currently available marketed drugs remains a global health concern. The cases of resistant tuberculosis patients are increasing day by day. Objective: The objective of this study is to highlight the need of developing shorter, simpler and tolerable drug regimens. Methods: In the present study, we synthesized various halo-substituted 2-aryloxyacetohydrazones via a series of reactions from halo-substituted phenols. All the compounds were characterized by using various spectroscopic methods, such as NMR, FT-IR, UV spectroscopy, etc. Results: All the synthesized hydrazones showed theoretically good interactions with enzyme enoyl reductase (pdb id: 4tzk). All the synthesized compounds (5a-5o) showed moderate to good activity (3.125-100 μg/mL) against Mycobacteria tuberculosis, H37RV strain. Conclusion: Our results would pave a new way for the development of more effective Anti-TB agents in the future.
Keywords: enoyl reductase